2021
DOI: 10.1039/d1cc02892h
|View full text |Cite
|
Sign up to set email alerts
|

Direct formation of 4,5-disubstituted carbazoles via regioselective dilithiation

Abstract: Carbazoles are widely exploited for their interesting photophysical and electronic properties, however bay (4,5-) functionalization is challenging, and previously inaccessible through carbazole C-H activation. We report a simple methodology which...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…For recent background literature on the chemistry of related carbazole-derived compounds and their applications, including syntheses of bioactive carbazoles, see: (Chakraborty et al, 1965;Bondock et al, 2019) and references cited therein. The syntheses of related benzo[def]carbazoles are described by Pocock et al (2021) and Geng et al (2016). For applications of benzo [def]carbazole derivatives, see: Vespa et al (2018), Atakan & Gunbas (2016) and Mys ´liwiec et al (2015).…”
Section: Chemical Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…For recent background literature on the chemistry of related carbazole-derived compounds and their applications, including syntheses of bioactive carbazoles, see: (Chakraborty et al, 1965;Bondock et al, 2019) and references cited therein. The syntheses of related benzo[def]carbazoles are described by Pocock et al (2021) and Geng et al (2016). For applications of benzo [def]carbazole derivatives, see: Vespa et al (2018), Atakan & Gunbas (2016) and Mys ´liwiec et al (2015).…”
Section: Chemical Contextmentioning
confidence: 99%
“…[NEXKOT (Ma et al, 2018); EZETOU (Hendsbee et al, 2016)] and the green solvent processing of organic chargetransporting materials (HUVQEX; Harding et al, 2020). Other compounds have benzo[def]carbazole derivatives as the skeleton, for instance, 4,5-iminophenanthrene (IMNPHN; Ern et al, 1971) , aka 4H-benzo[def]carbazole, capped [3]cyclo(2,6)benzo[def]carbazoledichloromethane solvate (ROZQAA;Mys ´liwiec et al, 2015), picenoporphyrins [QUQYAC01 (Nath et al, 2003); QUQYAC (Aihara et al, 2001)] and 4H-naphtho[1,2,3,4-def]carbazole (IWOBEE; Pocock et al, 2021). In addition, there is no alkynyl phenyl group on C8 and a phenyl group on C9 of the benzo-[def]carbazole as in the title compound in any structure found in the WebCSD search.…”
Section: Figurementioning
confidence: 99%
“…10,11 Carbazole is an electron-rich unit, providing good hole transporting properties, 12 high thermal and electrochemical stability, 13,14 high photoluminescence quantum yield (PLQY), 15 ease of functionalisation through different sites and tunable optical and electronic properties. 16 (Co)polymerisation of substituted carbazoles is also readily achieved yielding carbazole as a main-chain unit in luminescent and electroactive polymers. 17 However, it is important to note that commercial carbazole can contain trace amounts of isomeric impurities, identified as 1H-benzo[f]indole 18 and 5H-benzo[b]carbazole, 19 which have profound effects on the luminescent properties of the sample and derived products, notably giving enhanced PLQY and ultralong phosphorescence.…”
Section: Introductionmentioning
confidence: 99%
“…Kijima et al reported a synthetic strategy, including nitration, reductive ring closure, and dehydrogenation in sequence, to provide benzo[ def ]carbazole (Scheme 1g) from 9,10‐dihydrophenanthrene [33]. Very recently, a direct formation of 4,5‐disubstituted carbazoles through the use of n BuLi–TMEDA for lithiation and annulation with hexafluorobenzene gave the structure of 4 H ‐naphtho[1,2,3,4‐ def ]carbazole (Scheme 1h) [34].…”
Section: Introductionmentioning
confidence: 99%